PENERAPAN MODEL TIPE PAIR CHECK DISERTAI HAND OUT MATEMATIKA KELAS IX SMP - Iltavia, Iltavia; Oktria, Anggun Mitha (Universitas PGRI Sumatera Barat, 2020)
The problem that occurs in schools is the teacher-centered learning process, so that the goals of mathematics learning have not been achieved. To improve the learning outcomes of mathematics learning models need to be able to foster motivation and a strong desire for students to want to learn mathematics, one of which is the cooperative learning model Pair Check Type Accompanied by Hand Out. The population in this study was grade IX students of SMP N 1 Padangpanjang in 2016/2017 school year. The sample in this study was class IX D, the number of students was 30 people as the experimental class and class IX F as the control class, the number of students was 30 people. The type of research is the Randomized Control Group Only Design. Data acquisition of student learning outcomes in the cognitive domain is done by conducting tests on students who apply the Cooperative Learning Model Pair Check Type Accompanied by Hand Out with students who do not Apply the Cooperative Learning Model Pair Check Type Accompanied Hand Out. Based on the results of data analysis, the value of tcount = 1.86 and ttable = 1.67. Because tcount> ttable which means the research hypothesis is accepted which states the learning outcomes of students using Pair Check Cooperative Learning Model accompanied by Hand Out is better than student mathematics learning outcomes without using Pair Check Cooperative Learning Model Accompanied by Hand Out.